PENINGKATAN KINERJA MESIN PRESS BAGLOG JAMUR TIRAM MELALUI MODIFIKASI SISTEM KONTROL TEKANAN SILINDER MENGGUNAKAN MAGNET CLUTCH - Junaidi -; Riki Rahman; Sir Anderson; Eko Priyanda; Ramadani Safitri (Jurnal Ilmiah Poli Rekayasa, 2025)
Manual and semi-mechanical baglog production for oyster mushrooms in Indonesia, particularly in Padang West Sumatra, has suffered from low capacity, inconsistent quality, and operator fatigue. In this study evaluated performance improvements of a baglog pressing machine through modification of magnetic clutch integration and cylinder pressure control mechanism. The modification included installing a magnet clutch with supporting components (bushing, plate disk, clutch housing), motor and gearbox shafts, redesign of the pressing plate, and dual-opening chamber. Several technique was employed such as reducer speeds (30 to 90 rpm) and threaded rod adjustments distance (1.5 to 6.5 cm). Production capacity, cycle time, efficiency, and baglog density were investigated. Based on results, the  production capacity increased from approximately ±20 baglogs/hour (manually)to 120–270 baglogs/hour after modification, while the pressing cycle time decreased to as low as 13.33 s/baglog. The baglog density increased from about ±0.65 g/cm³ to ~0.709–0.900 g/cm³, with 80–90% process efficiency. Therefore, the magnetic clutch enabled precise engagement/disengagement control, enhancing safety and cycle precision. Overall, the modified machine provided an efficient for improving productivity, quality, and ergonomics for for SME’s sector mushroom production.